2013
DOI: 10.1155/2013/854261
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Source Water and Drinking Water in Urban Areas of Myanmar

Abstract: Myanmar is one of the least developed countries in the world, and very little information is available regarding the nation's water quality. This report gives an overview of the current situation in the country, presenting the results of various water-quality assessments in urban areas of Myanmar. River, dam, lake, and well water sources were examined and found to be of generally good quality. Both As and F− were present in relatively high concentrations and must be removed before deep wells are used. Heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The findings for HPC concur with other studies which reported that heterotrophic plate counts of bottled (noncarbonated) water are high and variable (Duranceau et al, 2012;Sakai et al, 2013). A study conducted in Bulawayo reported that, total viable counts where in the range 104 to 151 cfu/ml which is above the bottled water standard of < 100 cfu/ml (Okagbue et al, 2002).…”
Section: Resultssupporting
confidence: 88%
“…The findings for HPC concur with other studies which reported that heterotrophic plate counts of bottled (noncarbonated) water are high and variable (Duranceau et al, 2012;Sakai et al, 2013). A study conducted in Bulawayo reported that, total viable counts where in the range 104 to 151 cfu/ml which is above the bottled water standard of < 100 cfu/ml (Okagbue et al, 2002).…”
Section: Resultssupporting
confidence: 88%
“…Coliform concentration is commonly used as a measure of drinking water quality (Sakai, Kataoka, & Fukushi, ). To assess coliform concentrations, we used 3M Petrifilm Escherichia coli ( E .…”
Section: Methodsmentioning
confidence: 99%
“…Rural areas are the most affected, and residents resort to the collection of water from wells, ponds, springs, lakes, rivers and rainwater harvesting to meet their domestic water needs [19][20][21][22][23][24]. Water from such sources is often consumed without any form of treatment [12,19,21].…”
Section: Introductionmentioning
confidence: 99%